Cryptic gene pools in the Hypericum perforatum-H. maculatum complex: diploid persistence versus trapped polyploid melting - Scheriau, Charlotte; Nürk, Nicolai M.; Koch, Marcus (Annals of botany, 2017)
Background and Aims: In Central Europe Hypericum perforatum and Hypericum maculatum show significant hybridization and introgression as a consequence of Pleistocene range fluctuations, and their gene pools are merging on higher ploidy levels. This paper discusses whether polyploid hybrid gene pools are trapped in the ecological climatic niche space of their diploid ancestors, and tests the idea of geographical parthenogenesis.MethodsDNA sequence information of nuclear ribosomal DNA and plastid loci, ploidy level estimates and ecological niche modelling are used to characterize the various diploid and polyploid gene pools and unravel spatio-temporal patterns of gene flow among them.Key ResultsOn the diploid level, the three gene pools are clearly distinct between and within species of H. perforatum (two gene pools) and H. maculatum, and their divergence dates back to the first half of the Pleistocene. All polyploids in Central Europe show high levels of past and contemporary gene flow between all three gene pools. The correlation of genetic and geographical distances breaks down if the latter is larger than 250 km, indicating recent and ongoing gene flow. The two species are ecologically differentiated, but in particular hybrids among all three gene pools do not show significant niche differences compared to their parental gene pools, except for some combinations with H. maculatum.ConclusionsInter- and intraspecific gene flow between inter- and intra-species gene pools is limited on the diploid level, and the geographical distribution of the diploids largely reflects Pleistocene evolutionary history. Secondary contact promoted hybridization and introgression on the polyploid level, enabling offspring to escape the diploid gene pools. However, the hybrid polyploids do not show significant niche differences compared to their diploid progenitors. It is concluded that the observed absence of niche divergence has precluded further differentiation and geographical partitioning of new polyploid lineages being effectively separated from the parental lines. The predominantly apomictic reproducing polyploids are trapped in the polyploid gene pool and the ecological climatic niche space of their diploid ancestors.
Gesehen am 23.04.2018